The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/essoar.10501942.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does the air-sea coupling frequency affect convection during the MJO passage?

Abstract: The importance of air-sea coupling in the simulation and prediction of the Madden-Julian Oscillation (MJO) has been well established. However, it remains unclear how air-sea coupling modulates the convection and related oceanic features on the subdaily scale. Based on a regional cloud-permitting coupled model, we evaluated the impact of the air-sea coupling on the convection during the convectively active phase of the MJO by varying the coupling frequency. The model successfully reproduced the atmospheric and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Under strongly suppressed conditions, a thin ocean mixed layer combined with intense diurnal surface heating can induce diurnal SST perturbations of 1–3 K. Nighttime surface cooling drives convective overturning of the ocean mixed layer, mixing some of the daytime‐accumulated heat below the mixed layer; the remaining heat yields a warmer upper ocean at the next day's sunrise than the previous day's sunrise (Anderson et al, 1996). Thus, the SST diurnal cycle rectifies onto the intraseasonal scale (e.g., Bernie et al, 2005; Zhao & Nasuno, 2020).…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Under strongly suppressed conditions, a thin ocean mixed layer combined with intense diurnal surface heating can induce diurnal SST perturbations of 1–3 K. Nighttime surface cooling drives convective overturning of the ocean mixed layer, mixing some of the daytime‐accumulated heat below the mixed layer; the remaining heat yields a warmer upper ocean at the next day's sunrise than the previous day's sunrise (Anderson et al, 1996). Thus, the SST diurnal cycle rectifies onto the intraseasonal scale (e.g., Bernie et al, 2005; Zhao & Nasuno, 2020).…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
“…L. Zhou and Murtugudde (2020) found that SST anomalies up to +0.6 K northwest of Australia during MJO suppressed conditions generate anomalous cyclonic circulations and moisture advection that promote the MJO convective “detour” south of the MC. In regional coupled simulations, Zhao and Nasuno (2020) found that the rectification of diurnal SST variability associated with ocean mixed‐layer shoaling onto intraseasonal SST perturbations was more important for MJO propagation than the diurnal SST itself.…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Years of the Maritime Continent (YMC 1 ) is a multiyear (from 2015 to present) international program with participants from more than 15 countries. Its goal is to improve the understanding of the local oceanic and atmospheric multiscale variability of the Indo-Paci c maritime continent (MC), and the initial results have been published [2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%